Study on the stable preparation and optimization treatment of DWS N-type single-crystal silicon pyramid arrays - YuXin Zou; Xuan Liu; Mingjun Wang; Yating Song; Huan Liu; Shihao Hong; Fengshuo Xi (Materials for Renewable and Sustainable Energy)
Abstract In the current work, the effect of the surface phase structure of silicon wafer on the copper assisted chemical etching (Cu-ACE) behavior was investigated by adopting N-type monocrystal silicon with different thickness as raw material. An inverted pyramid structure was prepared with the method of Cu-ACE, which exhibited a mild reaction temperature with the reflectance reaching as low as 6.34%. Furthermore, cetyltrimethylammonium bromide (CTAB) was employed as an additive to optimize the Cu-ACE process. The study revealed that CTAB molecules could adsorb Cu2+ near the silicon wafer surface in the HF/Cu(NO3)2/H2O2 solution, thereby promoting the deposition of copper particles and ensuring a uniform etching reaction. When 3 mg of CTAB was added to 100 mL of etching solution, the inverted pyramid structure showed larger dimensions and was more uniformly distributed, an excellent antireflection effect was achieved with the reflectance significantly reduced from 10.8% to 4.6%. This process could stably fabricate inverted pyramid structures, and is expected to advance the development of high-efficiency single-crystal solar cells in the future.